Value of biodiversity on Patagonian rangeland: Estimation via a Hedonic Price Index - Duarte Guardia, Sandra; Peri, Pablo Luis; Martínez Pastur, Guillermo; Lasagno, Romina; Lencinas, Maria Vanessa; Thomas, Evert; Ladd, Brenton (Elsevier, 2024)
Plant diversity has long been linked to an increase in ecosystem productivity and function, but concrete examples in which ecosystem services are linked to diversity at the scale at which management decisions are taken are rare. We specifically tested for a correlation between plant diversity and provisioning ecosystem services estimated via the potential to produce meat and wool. We also tested whether higher levels of plant diversity conferred higher levels of ecosystem resistance to global change drivers, measured as the ability to sustain productivity across time. This was achieved by analyzing the interactive effects of a range of environmental variables on annual net primary production in a network of long-term biodiversity plots in Southern Patagonia. We found evidence of a positive correlation between plant diversity and plant productivity, which we relate to the ability to produce wool and meat from livestock. We also found evidence of a link between ecosystem resistance and diversity, though the effect was modest. The instrumental (economic) valuation presented doesn't account for the full range of values that rangeland in southern Patagonia generates. Nevertheless, these calculations do provide a starting point for broadening the discussion around the importance and value of natural capital in southern Patagonia. The results are consistent with theory and suggest that plant diversity has instrumental and monetary value as well as insurance value that may increase the resistance of rangeland ecosystems to global change drivers.